2015
DOI: 10.3892/ijmm.2015.2292
|View full text |Cite
|
Sign up to set email alerts
|

Arnebin-1 promotes angiogenesis by inducing eNOS, VEGF and HIF-1α expression through the PI3K-dependent pathway

Abstract: Arnebin-1, a naphthoquinone derivative, plays a crucial role in the wound healing properties of Zicao (a traditional wound healing herbal medicine). It has been noted that Arnebin-1, in conjunction with vascular endothelial growth factor (VEGF), exerts a synergistic pro-angiogenic effect on human umbilical vein endothelial cells (HUVECs) and accelerates the healing process of diabetic wounds. However, the mechanisms responsible for the pro-angiogenic effect of arnebin-1 on HUVECs and its healing effect on diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…AKT and MAPK signal pathways play a vital role in angiogenesis , Zeng et al 2015, Lv et al 2016. In this study, we also found that phosphorylated level of AKT and ERK in HUVECs increased notably after treatment with CM-48h ( Fig.…”
Section: Menscs-cm Activates Akt and Erk Pathways Of Endothelial Cellsupporting
confidence: 61%
See 1 more Smart Citation
“…AKT and MAPK signal pathways play a vital role in angiogenesis , Zeng et al 2015, Lv et al 2016. In this study, we also found that phosphorylated level of AKT and ERK in HUVECs increased notably after treatment with CM-48h ( Fig.…”
Section: Menscs-cm Activates Akt and Erk Pathways Of Endothelial Cellsupporting
confidence: 61%
“…Several studies had found that stem cells could paracrine a panel of cytokines and growth factors, contributing to repair of injured tissues (Kinnaird et al 2004a, Boomsma & Geenen 2012, Rahbarghazi et al 2013. AKT and MAPK signal pathway had been proved to play a vital role in angiogenesis , Zeng et al 2015, Lv et al 2016. Interestingly, we found that AKT and ERK could be activated by MenSCs-CM and the transcriptional expression level of eNOS, VEGFA, VEGFR1, VEGFR2 and TIE2 in HUVECs, which are the downstream targets of AKT and ERK pathway, increased after MenSCs-CM treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Serine-threonine protein kinase AKT is a major downstream target of PI3K for regulating tumor growth and angiogenesis (37,38). For instance, PI3K/AKT may regulate angiogenesis by several downstream targets such as mTOR/p70S6K1, FOXO, NOS, and GSK-3β (39)(40)(41).A study has reported that Arnebin-1 promotes angiogenesis by inducing eNOS, VEGF and HIF-1 expression through the PI3K-dependent pathway (42).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that PC3 and DU145 cells transfected with the Flag‐INPP4B plasmid showed significantly decreased protein levels of p‐Akt, but this had no significant influence on the total protein levels of Akt. It was confirmed that PI3K/Akt pathway functions upstream of VEGF . Therefore, we assumed that INPP4B decreased VEGF secretion through inhibiting the activation of the PI3K/Akt signalling pathway.…”
Section: Discussionmentioning
confidence: 57%